Preparation, Spectral Investigation, Thermal Analysis, Biochemical Studying of New (Oxadiazole - Five Membered Ring)- Ligands - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
A series of oxadiazole- Azo ligands have been synthesized via  many  steps  sequence. Oxadiazole -azo  ligands   were prepared through   reacting  azo–oxadiazole  derivatives  with phenol  heterocyclic  derivatives  diazotized   then  coupled   via   coupling  reaction  followed  by  cyclization  reaction   to  yield   azo- heterocycles   derivatives   which  act   five  membered  ring. The structures of the newly  prepared    Ligands  were  identified   through  more  than   technique  like (1H NMR, IR and Mass spectra) ,(Thermal ,microbial  assay ) for  all  ligands.Keywords: Oxadiazole, Thiosemicarbazide, Thiadiazol, Cyclization, Azo,Imidazole, Oxazole, Thiazole.